A Social Network Analysis of the The Lord of The Rings' Trilogy - Aires, Victória Patrícia; Almeida, Thais G.; Nakamura, Fabíola Guerra; Nakamura, Eduardo Freire (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2017)
Social networks provide mechanisms to represent and investigate different kinds of system like biological and social. In this work, our aim is to explore the characteristics of complex networks extracted from the books and movies of The Lord Of The Rings’ Trilogy. We use centrality measures (e.g., PageRank, Betweenness, Weighted Degree) to identify influential characters and the Louvain’s algorithm to identify social nuclei. The results show that the communities identified reflect the story’s main nuclei, and that in the different source medias the characters identified as more influential remain the same. In addition, we make a parallel between the differences and similarities of books (in Portuguese and English) and movies.